(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Few longitudinal studies have been done on the perception of patients about physical therapy care, through a questionnaire where it was possible to survey the perception of care at the Health Care Center of UNEC (CASU) - Campus Nanuque/MG. Objective: This study was carried out with the purpose of analyzing the perception of patients about the physiotherapeutic care dedicated to them by Physical Therapy trainees at the Health Care Center of UNEC (CASU) Campus of Nanuque/MG. Methodology: Through a descriptive and exploratory quantitative approach composed of 35 patients from CASU, where the instrument used for the study was the questionnaire adapted from the survey "Evaluation of the satisfaction of users of physiotherapy services", containing 15 closed questions. Results: When analyzing the data obtained, the vast majority of patients (77.17%) considered the attributes of physical therapy care very satisfactory. It is correct to consider that the conducts were followed adequately due to the high percentages defined as excellent (62.86%) to the results obtained with the physiotherapeutic treatment. Conclusion: The study was of great importance to have a survey of the perception of patients obtained through physical therapy and showed a population satisfied with the services it has been receiving, in this case, at the Health Care Center of UNEC (CASU).